Ottoman Civil Officialdom : A Social History - Findley, Carter Vaughn (Book collections on Project MUSE., 2014)
In this sequel to his highly acclaimed Bureaucratic Reform in the Ottoman Empire, Carter Findley shifts focus from the organizational aspects of administrative reform and development to the officials themselves. A study in social history and its cultural and economic ramifications, Findley's new book critically reassesses Ottoman accomplishments and failures in turning an archaic scribal corps into an effective civil service. Combining scrutiny of well-documented individuals with analyses of large groups of officials, Findley considers how much the development of civil officialdom ben.